2018
DOI: 10.1021/acssuschemeng.8b01705
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Heavy Metal Releases from Photovoltaic Panels and Quantum Dot Films: Hazardous Waste Concerns or Not?

Abstract: To determine if there are potential concerns related to the environmental end-of-life impacts of photovoltaic (PV) or quantum-dot display (QD) technologies, the goal of this study was to assess the magnitude of heavy metal leaching using simulated landfill methodologies from devices in an attempt to forecast the lifecycle environmental impacts of subsequent generations QD-enabled PV technologies. The underlying hypotheses are (H1) existing PV and QD thin-film technologies do not release heavy metals at concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…S1). 23 While the patent was not explicit on the QD core/shell synthesis, it did mention that CdSe was an exemplary material for QDs, preferably with the presence of both CdS and ZnS shells. 9 We hypothesize that these QDs possess a cadmium selenide (CdSe) core for narrow emission, an alloyed cadmium sulfide zinc sulfide (CdS/ZnS) shell for enhancement of quantum yield and stability.…”
Section: Resultsmentioning
confidence: 99%
“…S1). 23 While the patent was not explicit on the QD core/shell synthesis, it did mention that CdSe was an exemplary material for QDs, preferably with the presence of both CdS and ZnS shells. 9 We hypothesize that these QDs possess a cadmium selenide (CdSe) core for narrow emission, an alloyed cadmium sulfide zinc sulfide (CdS/ZnS) shell for enhancement of quantum yield and stability.…”
Section: Resultsmentioning
confidence: 99%
“…13 Spent PV modules, particularly those of older generations, could potentially be classified as borderline hazardous waste under the Resource Conservation and Recovery Act (RCRA) 14 due to the presence of toxic heavy metals (i.e., Pb in the solder of c-Si). 13,15 However, a detailed screening-level risk assessment study by the International Energy Agency (IEA) revealed that exposure point concentrations of Pb for c-Si PV are at least one order of magnitude below U.S. EPA health screening values in soil, air, and water if modules are placed in non-sanitary landfills under worst-case leaching scenarios. 16 Recently, PV module waste was reclassified under the less restrictive Universal Waste program in California to promote module recycling and reuse at the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…"Optimistic" scenarios represent an ambitious outlook for improving PV process related parameters (i.e., lifetime and efficiency). Additional details on parameters are in Table2optimistic 10% reuse of retired modules in a second life of15 years to reflect growth in module spares and progress in reuse/repair knowledge. In the absence of any recycling infrastructure, about 38.4 million MT of solar glass waste and 5.3 million MT of aluminum waste could be eliminated through 2100 compared with the baseline scenario.…”
mentioning
confidence: 99%
“…22 A QD-containing Kindle (Amazon) film leached only 10% of its Cd after the waste extraction test (WET) using citric acid at pH 5. 23 However, these studies provide limited information on how QDs are transformed because they assess an entire product in which QDs cannot be separated from the encapsulating solid matrix and do not allow for extraction of QD materials necessary for in-depth characterization and fate analysis. Additionally, limited effort was devoted to low pH exposures, despite their environmental and biological relevance.…”
mentioning
confidence: 99%
“…For example, a study on a QD-containing polymer prototype for light-emitting diodes (QD Vision) indicated that after 30 days, 7% Cd leaching under near-neutral conditions (pH 5 or 1 mM H 2 O 2 ) occurred . A QD-containing Kindle (Amazon) film leached only 10% of its Cd after the waste extraction test (WET) using citric acid at pH 5 . However, these studies provide limited information on how QDs are transformed because they assess an entire product in which QDs cannot be separated from the encapsulating solid matrix and do not allow for extraction of QD materials necessary for in-depth characterization and fate analysis.…”
mentioning
confidence: 99%